Improving Healthcare Outcomes in Hospitals Using Lean Six Sigma: A Review - AlMahri, Aysha Ali (2022)
A healthcare organization that applies the Lean Six Sigma concepts can find and fix issues with the way it delivers healthcare. No part of the hospital is excluded, and procedures can be reviewed starting with the moment a patient enters the emergency room and continuing through the admissions process, the inpatient stay, the discharge process, and any step in between including outpatient clinics. Improving the process at each step along the route have the potential to affect productivity, result in billing errors, and lower the organization's revenue capture. Lean Six Sigma can help a hospital achieve its budgetary objectives in this regard. According to our research, applying lean six sigma is a fairly reliable way to get better medical and financial results if done appropriately.